GENE EXPRESSION PROFILING AND EXPANDED IMMUNOHISTOCHEMISTRY TESTS TO GUIDE SELECTION OF CHEMOTHERAPY REGIMENS IN BREAST CANCER MANAGEMENT: A SYSTEMATIC REVIEW. (10th May 2017) - Scope, Alison; Essat, Munira; Pandor, Abdullah; Rafia, Rachid; Ward, Sue E.; Wyld, Lynda; Cross, Simon; Woods, Helen Buckley
Abstract : Objectives: The aim of this report was to assess the clinical effectiveness of two Gene expression profiling (GEP) and two expanded immunohistochemistry (IHC) tests compared with current prognostic tools in guiding the use of adjuvant chemotherapy in patients with early breast cancer. Methods: A systematic review of the evidence on clinical effectiveness of OncotypeDX, IHC4, MammaPrint, and Mammostrat, compared with current clinical practice using clinicopathological parameters, in women with early breast cancer was conducted. Ten databases were searched to include citations to May 2016. Results: Searches identified 7, 064 citations, of which forty-one citations satisfied the criteria for the review. A narrative synthesis was performed. Evidence for OncotypeDX demonstrated the impact of the test on decision making and there was some support for OncotypeDX predicting chemotherapy benefit. There were relatively lower levels of evidence for the other three tests included in the analysis. MammaPrint, Mammostrat, and IHC4 tests were limited to a small number of studies. Limitations in relation to study design were identified for all tests. Conclusions: The evidence base for OncotypeDX is considered to be the most robust. Methodological weaknesses relating to heterogeneity of patient cohorts and issues arising from the retrospective nature of the evidence were identified. Further evidence is required for all of the tests using prospective randomized controlled trial data.